Indirect COVID-19 health effects and potential mitigating interventions: Cost-effectiveness framework. - Sigal Maya; James G Kahn; Tracy K Lin; Laurie M Jacobs; Laura A Schmidt; William B Burrough; Rezvaneh Ghasemzadeh; Leyla Mousli; Matthew Allan; Maya Donovan; Erin Barker; Hacsi Horvath; et al. (PLoS ONE)
Background The COVID-19 pandemic led to important indirect health and social harms in addition to deaths and morbidity due to SARS-CoV-2 infection. These indirect impacts, such as increased depression and substance abuse, can have persistent effects over the life course. Estimated health and cost outcomes of such conditions and mitigation strategies may guide public health responses. Methods We developed a cost-effectiveness framework to evaluate societal costs and quality-adjusted life years (QALYs) lost due to six health-related indirect effects of COVID-19 in California. Short- and long-term outcomes were evaluated for the adult population. We identified one evidence-based mitigation strategy for each condition and estimated QALYs gained, intervention costs, and savings from averted health-related harms. Model data were derived from literature review, public data, and expert opinion. Results Pandemic-associated increases in prevalence across these six conditions were estimated to lead to over 192,000 QALYs lost and to approach $7 billion in societal costs per million population over the life course of adults. The greatest costs and QALYs lost per million adults were due to adult depression. All mitigation strategies assessed saved both QALYs and costs, with five strategies achieving savings within one year. The greatest net savings over 10 years would be achieved by addressing depression ($242 million) and excessive alcohol use ($107 million). Discussion The COVID-19 pandemic is leading to significant human suffering and societal costs due to its indirect effects. Policymakers have an opportunity to reduce societal costs and health harms by implementing mitigation strategies.